The Influence of Ease of Use, Practicality, and Product Information on Generation Z Consumer Purchase Decisions on the Shopee Application in Makassar City - Adel Gedis Mangngappi; Amir Jaya; Jerliyen Pramita Londong (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
The development of digital technology and the rapid growth of e-commerce have changed consumer shopping behaviour, especially among Generation Z, who are highly dependent on digital platforms. This study aims to analyse the influence of convenience, practicality, and product information on the purchasing decisions of Generation Z consumers who use the Shopee application in Makassar City. Purposive sampling was utilised to pick 100 respondents for the quantitative, explanatory research design study. Using the SmartPLS 4 program, Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to analyse the data. Convenience had a positive and significant impact on purchasing decisions (β = 0.370; t = 3.069; p = 0.002), practicality had a positive and significant impact (β = 0.312; t = 2.073; p = 0.038), and product information had a positive but not significant impact (β = 0.259; t = 1.873; p = 0.061). With an R-Square value of 0.831, the study model has good predictive potential. On the Shopee platform, Generation Z's purchase decisions are primarily influenced by convenience.